Relationship between Sociodemographic Factors and Teacher Burnout Syndrome in International Schools in Nairobi County - Joan Mukami (IJRDO- Journal of Educational Research, 2021)
Teaching can be very demanding, as teachers must cope with an array of academic, personal, and social challenges. When the demands persist and the coping strategies are insufficient to address the challenges, stress is eventually provoked. In the international schools set up, burnout is regarded as a state of emotional and physical depletion that results from conditions that are attributable to teaching. Burnout is characterized by three symptoms – depersonalization, emotional exhaustion, and reduced personal accomplishment. According to the cognitive activation theory of stress, health is dependent on how well individuals can adapt to physical, psychosocial, and environmental challenges (Ursin & Eriksen, 2004). Undoubtedly, teaching in international schools is characterized by various job demands that underpin the feeling of the heavy workload that ranges from regular meetings, administrative paperwork to being subjected to constant reforms to meet high-performance demands. Sociodemographic factors could be attributed to the surging levels of teacher burn out syndrome in international schools.